Illocutionary Acts Of The 100 Covid-19 Health Protocol Campaign Posters On Facebook Status Updates (A Netnographic Study) - Ratna Susanti; A. Anditha Sari; Basnendar Herry Prilosadoso (Jurnal Ad'ministrare, 2022)
This study aims to identify the types of illocutionary speech acts contained in 100 poster designs containing appeals for the prevention of Covid-19 and the application of health protocols posted on social media Facebook. This study uses a qualitative descriptive method by applying the data collection techniques of Miles, Huberman, and Saldana, namely data condensation, data display, and conclusion. This study uses Searle's theory of illocutionary speech acts to analyze the collected data. The theory includes the types of illocutionary speech acts, namely directive, assertive, expressive, commissive, and declarative. The results of this study indicate that of the 100 poster designs analyzed, there were 64 posters containing directive speech acts, 27 posters containing assertive speech acts, 8 posters containing expressive speech acts, and 1 poster containing commissive speech acts. The large number of posters containing declarative speech acts indicates that the poster is aimed at hearers or audiences to do or carry out something related to the prevention of Covid-19 and the application of strict health protocols. This is in line with the purpose of the poster, which is persuasive, which means it can influence people who see or read it.